2011
DOI: 10.1177/0009922811430342
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Modified Pediatric Early Warning System Score

Abstract: The Pediatric Early Warning System (PEWS) score may be useful for detection of deterioration in clinical condition. In this retrospective study, the cases were patients transferred to the pediatric intensive care unit (PICU), and controls were those not transferred to the PICU. The maximum PEWS score in both groups were analyzed using Mann-Whitney U test and receiver operating characteristic curve (ROC). The study population included 100 cases and 250 controls. There was no difference in the age of cases and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 21 publications
1
55
0
5
Order By: Relevance
“…As an early indicator of deterioration leading to the call of the rapid response team or code blue, the BPEWS showed sensitivity of 85.5% for score ≥ 4 (12) . For ICU transference, the sensitivity and specificity of a BPEWS modified version were of 62% and 89%, respectively (14) . In the prediction of the need for transference to the ICU in 24 hours from admission, the BPEWS presented sensitivity of 68.4% and specificity of 81.6% (26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an early indicator of deterioration leading to the call of the rapid response team or code blue, the BPEWS showed sensitivity of 85.5% for score ≥ 4 (12) . For ICU transference, the sensitivity and specificity of a BPEWS modified version were of 62% and 89%, respectively (14) . In the prediction of the need for transference to the ICU in 24 hours from admission, the BPEWS presented sensitivity of 68.4% and specificity of 81.6% (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The mean time of a critical score, shortly before the event was 30 minutes (12) . To validate a BPEWS modified version, a retrospective study conducted with 100 patients in a case group (transferred from the medical-surgical ward to the ICU) and 250 in a control group (not transferred to the ICU) from 0 to 14 years, found that the maximum BPEWS score was significantly higher in the case group (case: 2.95 ± 1.5 versus control: 1.4 ± 0.8, p > 0.0001) (14) . After the translation and adaptation process for obtaining the BPEWS-Br, the need for a more consistent validation study from the application of the score in the reality experienced by the nurses and doctors in the Brazilian hospital context is highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various pediatric early warning systems have been studied. [14][15][16][17][18] The effect of combined use of pediatric early warning systems for early detection of critical worsening in clinical status and rapid response systems for early treatment is yet to be determined. In addition, mandatory RRT activation determined by using a pediatric early warning scoring system algorithm may further enhance the effectiveness of RRT use.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of EWS are now commonly used at major adult and pediatric medical centers. 12,13 These EWS are well validated, [14][15][16][17][18] increase identification of deteriorating children, 19 and supplement improvements to patient safety. 20 EWS can be combined with rapid response teams (RRT) that decrease cardiac arrest [21][22][23] and significantly decrease mortality [24][25][26][27] in both prospective studies 28 and across multiple settings.…”
mentioning
confidence: 99%